Der Sog des Neuen und der Schock des Alten Jahrbuch Technikphilosophie 2024

The role of phenylnitrene in the formation of polycyclic aromatic nitrogen containing hydrocarbons - Arns, Rahel

Mit Kleidung lügen. Über Vestimentäres und Modisches im Vormärz - Kraft, Kerstin

Zur Mode im deutschen Kulturraum. Materialien, Textilien, Texte. - Kraft, Kerstin; Haase, Birgit

N2O oxidized combustion of ethylene: Detailed laminar flame structure and the significance of oxidizer decomposition kinetics for modeling - Hoener, Martin; Bierkandt, Thomas; Shaqiri, Shkelqim; Kasper, Tina (Proceedings of the Combustion Institute)

Operative Beziehungen erkennen, beschreiben und nutzen - Initiierung von Lernprozessen unter Einbeziehung der App "Rechenfeld" - Dettelbach, Andrea; Häsel-Weide, Uta (Förderung prozessbezogener Kompetenzen mit digitalen Medien. Mit mathematischen Objekten und Werkzeugen arbeiten.)
Ein zentrales Ziel des Mathematikunterrichts der Grundschule ist es, Kinder anzu- regen, rechnerisch zu denken, anstatt zählend zu rechnen. Dies erfordert ein Ver- ständnis für mathematische Operationen sowie die Fähigkeit, Aufgaben in Bezie- hung zueinander zu setzen und Merkmale der Aufgaben zu berücksichtigen. Dazu können digitalgestützte Lernumgebungen zur Förderung des Verständnisses der Ad- dition beitragen, die Kinder anregen, Aufgaben zu verändern und die in verschiede- nen Darstellungen erkennbaren Beziehungen zu beschreiben und zu erklären. Der Beitrag erläutert Gestaltungskriterien und zeigt erste Erkenntnisse in Bezug auf die von Kindern erkannten operativen Beziehungen.

Accents of English in English language teaching in Germany: a corpus-phonological approach to textbook analysis - Scheiwe, Lisa
In der vorliegenden Arbeit wird die Darstellung von drei ausgewählten Akzenten des Englischen in den Audio Materialien deutscher Englisch-Schulbücher untersucht. Dabei verfolgt diese Arbeit einen Korpus-phonologischen Ansatz um die Darstellung des Britischen, Amerikanischen, und Australischen Englisch zu untersuchen. Dabei wird das Augenmerk auf die Akzente Received Pronunciation, General American, und Standard (Mainstream) Australian English in den drei in NRW genutzten Lehrwerken English G Access, Green Line, und Camden Town gelegt. Das phonologische Schulbuchkorpus umfasst 3 Stunden, 36 Minuten, und 40 Sekunden Audio Material. Insgesamt umfasst das Korpus 54 Sprecher*innen für die asugewählte phonologische Merkmale für jeden untersuchten Akzent analysiert werden. Die Ergebnisse der Arbeit zeigen, dass die drei Lehrwerke einige phonologische Merkmale der Akzente Received Pronunciation, General American, und Standard (Mainstream) Australian English darstellen, dies aber nciht durchgängig für alle Sprecher*innen. Dennoch zeigt die Arbeit, dass die Schulbücher und die Audio Materialien den Schüler*innen eine effektive und praktische Möglichkeit bieten, die Variation der Englischen Sprache kennenzulernen.

Ideology and the Microfoundations of Conflict - Müller, Veronika; Gries, Thomas
Abstract This book combines theoretical and empirical research across various academic disciplines, including economics, psychology, neuroscience, philosophy, and political science, to describe why individuals adopt political ideologies and how this choice can potentially exacerbate conflict and violence. Ideology is particularly important to conflict. Data on intra- and international conflict shows that the number of ideologically driven conflicts has increased tremendously in recent decades. Although some researchers have started to investigate extensively the link between ideology and conflict, they struggle to find holistic explanations through which ideologies might shape conflict. This book addresses this effort by providing an interrelated multidisciplinary framework to explain the multidimensional functions of ideology. It illustrates that ideologies are not only capable of shaping conflictual behavior or mobilizing political actors, but also of addressing human needs, desires, and preferences. Hence, this book seeks to explain how individuals adopt ideologies that match their underlying needs and preferences; that ideologies have the capacity to reconcile deprived psychological human needs; and that radical groups and organizations use ideologies to recruit individuals and pursue their objectives. To understand these relationships better and to apply the theoretical background to real-world situations, we include real-life cases that describe how depriving individuals of resources that satisfy their underlying needs and preferences can lead them to adopt particular ideologies that are disseminated by radical groups or organizations. These radical groups or organizations then make decisions, which can potentially lead to conflict onset and continuous long-term struggles.

Interdisciplinary collaboration in vocational education and training (VET). Opportunities and challenges for business and technical teachers - Koppius, Sebastian Niklas (Book of Abstracts)

Implementierung interdisziplinärer Kompetenzen in die berufliche Bildung: Herausforderungen für kaufmännische und gewerblich-technische Berufsschullehrer: innen - Ein DBR-Forschungsansatz. - Koppius, Sebastian Niklas

Interdisciplinary Collaboration in Vocational Education and Training (VET): Opportunities and Challenges for Business and Technical Teachers - Koppius, Sebastian Niklas

Der kaufmännisch-gewerblich-technische Diskurs zur Gestaltung von kooperativen Lehr-/ Lernarrangements - Einblicke aus einem Forschungsportfolio - Koppius, Sebastian Niklas

Die Ausbildung von morgen gestalten: Mit 5G und für 5G - Koppius, Sebastian Niklas; Schäfers, Johannes; Schuba, Kornelia

Bijective Volumetric Mapping via Star Decomposition - Hinderink, Steffen; Brückler, Hendrik; Campen, Marcel (ACM Transactions on Graphics)
A method for the construction of bijective volumetric maps between 3D shapes is presented. Arbitrary shapes of ball-topology are supported, overcoming restrictions of previous methods to convex or star-shaped targets. In essence, the mapping problem is decomposed into a set of simpler mapping problems, each of which can be solved with previous methods for discrete star-shaped mapping problems. Addressing the key challenges in this endeavor, algorithms are described to reliably construct structurally compatible partitions of two shapes with constraints regarding star-shapedness and to compute a parsimonious common refinement of two triangulations.

A Progressive Embedding Approach to Bijective Tetrahedral Maps driven by Cluster Mesh Topology - Nigolian, Valentin Zénon; Campen, Marcel; Bommes, David (ACM Transactions on Graphics)
We present a novel algorithm to map ball-topology tetrahedral meshes onto star-shaped domains with guarantees regarding bijectivity. Our algorithm is based on the recently introduced idea of Shrink-and-Expand, where images of interior vertices are initially clustered at one point (Shrink-), before being sequentially moved to non-degenerate positions yielding a bijective map (-and-Expand). In this context, we introduce the concept of the cluster mesh , i.e. the unexpanded interior mesh consisting of geometrically degenerate simplices. Using local, per-vertex connectivity information solely from the cluster mesh, we show that a viable expansion sequence guaranteed to produce a bijective map can always be found as long as the mesh is shellable. In addition to robustness guarantees for this ubiquitous class of inputs, other practically relevant benefits include improved parsimony and reduced algorithmic complexity. While inheriting some of the worst-case high run time requirements of the state of the art, significant acceleration for the average case is experimentally demonstrated.

Particle-induced Instabilities in Uniaxially Elongated Thermoplastic Polymer Blends - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

The influence of embedded fiber optic sensors on the global mechanical behavior of adhesively bonded joints - Hermelingmeier, Lucas; Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson (77th IIW Annual Assembly and International Conference on Welding and Joining)

Belgischer Symbolismus zum Be/Greifen nah. Museumskoffer zum Werk von Léon Spilliaert und George Minne.
Der belgische Symbolismus wurde in den letzten Jahrzehnten neu entdeckt. Während Künstler wie Léon Spilliaert und George Minne lange ein Geheimtipp waren, ziehen sie nun ein großes Publikum in ihren Bann. Dennoch gelten viele Werke dieser Kunstströmung bis heute aufgrund der sie prägenden anspruchsvollen Formensprache, verborgenen Bedeutungen und mystischen Visionen als ebenso anziehend wie unergründlich. Die hier vorgestellten siebzehn Museumskoffer bieten vielfältige Zugänge, sie in ihrem kulturellen und kunsthistorischen Kontext zu entdecken und zu verstehen: Sie machen kulturelles Lernen zu einem ganzheitlichen Erlebnis und öffnen Türen zu neuen Welten. Ergänzend stellt der Katalog Texte zum Medium ‚Museumskoffer‘, zum belgischen Symbolismus und weiteres relevantes Informationsmaterial zur Verfügung.
Keywords: Belgischer Symbolismus; Museumskoffer; León Spilliaert; George Minne

Mind Map zur Konzeption von Museumskoffern - Eikermann, Larissa (Belgischer Symbolismus zum Be/Greifen nah: Museumskoffer zum Werk von Léon Spiliaert und George Minne)
Keywords: Museumskoffer; Belgischer Symbolismus

Museumskoffer – Ein vielseitiges didaktisches Medium - Eikermann, Larissa (Belgischer Symbolismus zum Be/Greifen nah: Museumskoffer zum Werk von Léon Spiliaert und George Minne)